Exploration des activités biologiques de Retama retam - HAMDI CHERIF, Sid Ahmed (My University, 2022)
The present study aims to evaluate the antioxidant and anti-inflammatory activity of Retama retam extract. The antioxidant activity is evaluated by DPPH radical scavenging test. According to the results, the ethanolic extract of Retama retam exhibits a good antioxidant effect against this radical. The anti-inflammatory activity of this plant has been explored by two methods: the HRBC red blood cell membrane stabilization method and the protein denaturation inhibition test. The results obtained show that the ethanolic extract of Retama retam displayed an effect of the stability of the membranes of red blood cells of 79%. In addition, this extract exerts an inhibitory power of protein denaturation of 34%. From these results, it is deduced that Retama retam has good anti-inflammatory potential.
Keywords: Retama retam; Antioxidant effect; anti-inflammatory effect; protein denaturation; DPPH